Educating Ministers of Character: Building Character into the Learning Process in Ministerial Formation. Issue 1 (16th December 2013) - Heywood, David
Abstract : In partnership with other denominations in England, the Church of England is currently engaged in a collaborative exercise to design a suite of common curricula to guide ministerial education. This process has been the catalyst for fruitful discussion about the nature of ministerial education and in particular the role of character. This article examines the relationship of character and reflective practice and the kind of knowing that is implied by these. It shows how the understanding of learning required to see character development as integral to ministerial formation is well supported epistemologically and psychologically and explores the implications of these insights for the process of HE validation of ministerial education.